2013 Annual Report Conference on Electrical Insulation and Dielectric Phenomena 2013
DOI: 10.1109/ceidp.2013.6747454
|View full text |Cite
|
Sign up to set email alerts
|

Research of Dielectric spectroscopy on insulation ageing assessment of XLPE cables

Abstract: In this paper, the model cables are studied by means of frequency domain spectroscopy (FDS) which involves the measurement of capacitance, the real permittivity and dissipation factor as a function of frequency. Firstly, XLPE cable samples were carried out accelerated thermal ageing at 135 ć . Then ˈ frequency domain spectroscopy was investigated under laboratory condition, including different degree of thermal ageing and different test temperatures. Mechanism was analyzed using the theory of dielectric relaxa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The de-polymerization and oxidation byproducts consequent to thermal ageing can increase the permittivity [21][22][23]. It can be more significant at higher frequencies such as 2.5 kHz as used for PDIV measurement and even higher under very fast steep-fronted square waveform excitation due to the non-negligible spectral energy of the voltage waveform.…”
Section: A Capacitance and Dissipation Factor As A Function Of Therma...mentioning
confidence: 99%
See 1 more Smart Citation
“…The de-polymerization and oxidation byproducts consequent to thermal ageing can increase the permittivity [21][22][23]. It can be more significant at higher frequencies such as 2.5 kHz as used for PDIV measurement and even higher under very fast steep-fronted square waveform excitation due to the non-negligible spectral energy of the voltage waveform.…”
Section: A Capacitance and Dissipation Factor As A Function Of Therma...mentioning
confidence: 99%
“…Indeed, two factors can impact permittivity: thermal ageing and surface charge density caused by electrical stress with a steep-fronted waveform. The former can increase the permittivity in the long run [21][22][23] (Fig. 5).…”
Section: B Pdiv Analysis In Terms Of Thermal Ageing Rise Time and Pol...mentioning
confidence: 99%
“…It is believed that long-chain XLPE molecules break into short chains and thermal motion becomes intense during the aging process, which can result in more polar groups and carriers. These changes lead to more interfacial polarization (Maxwell–Wagner–Sillars), and make the dielectric relaxation phenomenon more obvious [ 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, it has been reported that the IC of a dielectric material can increase under thermal ageing phenomenon due to the depolymerization and oxidation byproducts. This can increase the permittivity of dielectric material and hence can contribute to increase capacitance [19][20][21]. Depolymerization is the process by which a polymer breaks down into smaller molecules.…”
Section: A Tanδ and Icmentioning
confidence: 99%